PENGARUH STRATEGI PEMBELAJARAN RELATING, EXPERIENCING, APPLIYING, COOPERATING, TRANSFERRING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI MIPA SMA ADABIAH 2 PADANG - Yesi Arifin (Jurnal Edukasi dan Penelitian Matematika, 2021)
The purpose of this research is to determine the mathematical concept understanding ability students who study with the REACT learning strategy and compare it with conventional learning in class XI SMA Adabiah 2 Padang. The type of this research is quasi-experimental with static group comparison design. The population in this research is students of class XI SMA Adabiah 2 Padang with the sample of class XI MIPA 3 as experimental class and XI MIPA 4 as the control clas. From the data analysis, the average value of experimental class was 85,08 and the control class average was 71,76. The result of the calculation of the hypothesis test with tcount is 5.512 and ttable is 2.032, because tcount>ttable (5,512>2,032), so it can be concluded that the proposed hypothesis is accepted. This means that the mathematical concept understanding ability students who study with the REACT learning strategy are better than the results of students mathematics learning with conventional learning in class XI SMA Adabiah 2 Padang. Keywords – Mathematical Concept Understanding, REACT